An Analysis of Challenges and Strategic Optimization in the Implementation of Coretax for Tax Reporting in Indonesia - Permatasari, Annisa Aprilia; Ramadhan, Pinolia; Wahono, Puji; Pahala, Indra (The Future of Education Journal, 2025)
This study aims to analyze the challenges faced in the implementation of the CoreTax system by the Directorate General of Taxes (DJP) and to formulate optimization strategies to enhance efficiency and compliance in tax reporting. A qualitative-descriptive approach was employed. The findings indicate that while CoreTax offers various advantages such as data integration, ease of access, and service transparency, its implementation requires gradual adjustments, improvements in technological infrastructure, and the strengthening of human resources to function optimally. The implementation of extensive public outreach, intensive training, and continuous supervision strategies is key to maximizing the benefits of CoreTax in supporting digitally driven tax administration reform. With the right approach, CoreTax is expected to improve taxpayer compliance and optimize state revenue in the future.